substance use and recidivism of intimate partner violence in Peru: A cross-sectional study. - Victor Roman-Lazarte Sr.; Enrique Moncada-Mapelli; Maryorie K Galeas-Torre; Luz A Roman; Maricela L Marcelo-Armas (Health Psychology Research)
# Background